Bank-advisor certification and willingness to pay for sustainable finance products - Katharina Holzheu; Tobias Wekhof (ETH Zurich, CER-ETH - Center of Economic Research, 2025)
We examine Swiss retail investors' willingness to pay (WTP) for sustainable finance products and the influence of bank advisor certification. In a hypothetical choice experiment with a randomized controlled trial (RCT), we assigned participants to either a priming treatment with a bank advisor certified in sustainable investing or a control group. We found a WTP between 1 and 1.5 percentage points of annual return for sustainable mutual funds, especially among financially literate investors. The presence of a certified green finance advisor further increased WTP between 0.2 and 0.8 percentage points, particularly for investors with low financial literacy.
Keywords: G11; G18; G41; G53; 330; sustainable investing; willingness to pay; financial literacy; sustainable financial literacy; conjoint analysis; certified financial advice; RCT